MIRERC 061/2025: ASSESSMENT OF KNOWLEDGE, ATTITUDE AND PRACTICES AMONG HEALTHCARE WORKERS IN THE ADOPTION OF MOLECULAR DIAGNOSTICS IN CANCER CARE AND TREATMENT IN KENYA. - MBURU, RUTH NDUTA; Dr. Frank Onyambu; Dr. Patrick Kubai, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Executive Summary Molecular diagnostics offers significant potential in enhancing cancer care and treatment through early detection, personalized therapies, and improved outcomes. In Kenya, where the cancer-related cases and deaths continue to increase, the adoption of Molecular diagnostics remains limited. Challenges such as inadequate knowledge, negative attitude, and poor practices among healthcare coupled with limited infrastructural components, play a significant role in the adoption of these techniques. This study aims to assess the Knowledge, attitudes, and practices of healthcare workers in the adoption of Molecular diagnostics for cancer care and treatment, with a focus on facility readiness and barriers in implementation. A cross-sectional analytical study will be conducted to assess healthcare workers, including oncologists, pathologists, and Nurses, across public and private facilities in Kenya. The facilities will be selected through a stratified random sampling process. Data will be collected using a structured questionnaire, focused group discussions, and Key Informant interviews to evaluate KAP regarding molecular diagnostics. The study is grounded in two theoretical frameworks: the Health Belief Model (HBM), which examines perceived benefits, such as early cancer detection, and perceived barriers, including the costs associated with the proposed molecular diagnosis. The Diffusion of Innovation (DOI) Theory explains adoption through the lenses of relative advantages, complexity, and observability. Quantitative data will be analyzed using descriptive statistics and logistic regressions to identify predictors of adoption, while qualitative data will be analyzed thematically to explore barriers and facilitators of the same. Ethical approval will be obtained from the Meru University Ethical Review Board (MIREC) and the National Commission for Science, Technology and Innovation (NACOSTEC), and data collection approvals from the different counties and respective health facilities. The study will assess the existing gaps in knowledge, attitudes, and practices that hinder the adoption of molecular diagnostics. The findings will inform targeted interventions such as training and workshops to enhance the adoption of Molecular diagnostics, which will ultimately reduce cancer-related mortality, hence improving care in Kenya